Acid and alkali resistant high-strength composite printing nickel screen and preparation method thereof

By adopting a multi-layer composite structural design on the printed nickel net, including the island-like columnar crystal structure nickel layer, chromium layer and crosslinked resin layer, the problem of insufficient acid and alkali resistance and mechanical strength in harsh environments is solved, and the performance is comprehensively improved and the application scope is expanded.

CN119640357AActive Publication Date: 2025-03-18HUAIAN TIANMA TEXTILE EQUIP CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510185317.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2025-03-18
Estimated Expiration
2045-02-19

AI Technical Summary

Technical Problem

When used in harsh environments such as strong acids and alkalis, the existing printed nickel mesh has insufficient acid and alkali resistance and mechanical strength, resulting in reduced performance and short service life.

Method used

Using a multi-layer composite structure design, the surface of the printed nickel mesh substrate is equipped with electroplated nickel layer, electroplated chromium layer and photosensitive resin layer in turn. The nickel layer contains an island-like columnar crystal structure and twin structure. The interface between the chromium layer and the nickel layer is wavy, and a highly crosslinked photosensitive resin layer is formed through a thiol-olefin click chemical reaction.

Benefits of technology

It significantly improves the acid and alkali resistance, mechanical strength and comprehensive performance of printed nickel mesh, extends the service life, reduces production costs, and expands its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640357A_ABST
    Figure CN119640357A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of printing nickel screens, in particular to an acid and alkali resistant high-strength composite printing nickel screen and a preparation method thereof. The composite printing nickel screen comprises a printing nickel screen base body, and a nickel electroplating layer, a chromium electroplating layer and a photosensitive resin layer are sequentially arranged on the surface of the printing nickel screen base body from inside to outside. The photosensitive resin layer is prepared from a polyurethane-acrylate prepolymer and sulfydryl silicon resin through a sulfydryl-olefin click chemical reaction; the preparation method comprises the steps that S1, a core mold is put into a first nickel plating electroplating solution for nickel plating, a nickel net is separated from the core mold, and a printing nickel net base body is obtained; s2, the printing nickel net base body is put into a second nickel plating electroplating solution for nickel plating, and the surface of the printing nickel net base body is covered with an electroplated nickel layer; then plating chromium; and S3, preparing a photosensitive resin layer on the surface of the electroplated chromium layer. According to the invention, the strength, acid and alkali resistance and other properties of the printing nickel screen are comprehensively improved, the application problem of the traditional technology in a severe environment is solved, and a new technical path is provided for the high-performance printing nickel screen.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of printed nickel meshes, and in particular to an acid- and alkali-resistant high-strength composite printed nickel mesh and a preparation method thereof. Background Art

[0002] As a key functional material in the fields of textile printing and dyeing, electronic circuit manufacturing, etc., the performance of printed nickel mesh directly affects product quality and production efficiency. In practical applications, printed nickel mesh often needs to work for a long time in harsh environments such as strong acid and strong alkali, while bearing high-intensity mechanical stress and wear. Therefore, improving the acid and alkali resistance and mechanical strength of printed nickel mesh has become an urgent need in the industry. High acid and alkali resistance can extend the service life of printed nickel mesh in corrosive environments, reduce the frequency of replacement, and significantly reduce production costs; while excellent mechanical strength can ensure that the printed nickel mesh maintains stable performance under high pressure and high-speed operation conditions, and improve printing accuracy and efficiency. In addition, the development of acid and alkali resistant and high-strength printed nickel mesh will also expand its application range, such as use in special environments in the fields of chemical industry and medical treatment, and promote the upgrading of related industrial technologies. Therefore, the research and development of composite printed nickel mesh with high acid and alkali resistance and high mechanical strength has important practical significance and application value.

[0003] However, the printed nickel mesh on the market still has obvious deficiencies in acid and alkali resistance and mechanical strength. The traditional single nickel layer structure is difficult to meet the requirements of high corrosion resistance and high strength at the same time, while the simple multi-layer composite structure often leads to performance degradation due to the loose bonding between the layers. For example, the Chinese patent with patent number CN212097930U discloses an ecological printed nickel mesh, but its acid and alkali resistance and strength still need to be improved. The root cause of these problems lies in the limitations of material design and preparation process. First, it is difficult for the traditional electroplating process to accurately control the microstructure of the nickel layer, which affects its mechanical properties and corrosion resistance; secondly, the interface design of the multi-layer structure is not optimized enough, and the synergistic effect of each functional layer cannot be fully exerted; thirdly, the selection and preparation method of the surface protective layer are poor, and it is difficult to strike a balance between protection and functionality. Therefore, the development of new composite structure design and advanced preparation process to achieve the synergistic improvement of acid and alkali resistance and mechanical strength of printed nickel mesh has become the focus and difficulty of current research. Summary of the invention

[0004] (1) Technical issues solved The purpose of the present invention is to provide an acid- and alkali-resistant high-strength composite printed nickel mesh and a preparation method thereof, so as to solve the problem that the current printed nickel mesh is insufficient in strength and acid- and alkali-resistant performance.

[0005] (2) Technical solution In order to achieve the above object, the present invention provides the following technical solutions: An acid-base resistant high-strength composite printed nickel mesh, comprising a printed nickel mesh substrate, wherein the surface of the printed nickel mesh substrate is sequentially provided with an electroplated nickel layer, an electroplated chromium layer and a photosensitive resin layer from the inside to the outside; The photosensitive resin layer is obtained from polyurethane-acrylate prepolymer and mercapto silicone resin through mercapto-olefin click chemical reaction.

[0006] The composite printed nickel mesh of the present invention exhibits a significant synergistic effect through a multi-layer composite structure. The printed nickel mesh substrate and the electroplated nickel layer provide basic strength and corrosion resistance, the electroplated chromium layer increases the surface hardness and wear resistance, and the photosensitive resin layer further improves the comprehensive performance of the material.

[0007] The photosensitive resin layer is obtained by the thiol-olefin click chemical reaction of polyurethane-acrylate prepolymer and mercapto silicone resin. This reaction forms a highly cross-linked and chemically resistant composite resin layer, which gives the resin layer excellent mechanical strength and chemical stability, ensuring that it can be precisely cured during the printing process to form a high-resolution pattern. Among them, the polyurethane-acrylate prepolymer mainly provides excellent mechanical properties and flexibility, while the mercapto silicone resin mainly enhances the heat resistance and chemical stability of the material.

[0008] Furthermore, the electroplated nickel layer contains an island-like columnar crystal structure, and the average diameter of the columnar crystal structure is 50-150 nm; the electroplated nickel layer also contains a crystalline structure.

[0009] First, the electroplated nickel layer contains an island-like columnar crystal structure. This unique microstructure has multiple effects: on the one hand, the columnar crystal structure can effectively hinder dislocation movement and improve the yield strength and tensile strength of the material; on the other hand, the nanoscale gaps between the crystals can serve as a barrier for the diffusion of corrosive media, significantly improving the corrosion resistance of the material. In addition, this microstructure may also improve toughness and fatigue resistance, increase the surface area, and enhance the bonding force and stability between the coatings. The average diameter of the columnar crystals is in the range of 50~150nm. This size not only ensures sufficient structural stability, but also maintains a high specific surface area, which is conducive to subsequent functionalization or catalytic applications.

[0010] Secondly, the electroplated nickel layer also contains a Luan crystal structure. This special crystal morphology further enhances the mechanical properties and corrosion resistance of the coating. The presence of the Luan crystal structure makes the coating have higher hardness and toughness, while also improving the density of the coating, effectively blocking the penetration of corrosive media. In addition, the synergistic effect of the island-like growth columnar crystal structure and the Luan crystal structure improves the mechanical strength of the coating while maintaining good ductility and avoiding the problem of brittleness. This microstructure is also conducive to improving the thermal stability and fatigue resistance of the coating, extending the service life of the coating.

[0011] Furthermore, the interface between the electroplated nickel layer and the electroplated chromium layer is wavy.

[0012] The wavy interface between the electroplated nickel layer and the electroplated chromium layer of the present invention has the following advantages: first, this unique wavy interface design significantly enhances the interlayer bonding strength. The wavy interface greatly increases the contact area between the two layers, provides more mechanical interlocking points, and thus enhances the bonding force between the nickel layer and the chromium layer. This enhanced interface bonding not only improves the overall strength of the composite printed nickel mesh, but also effectively prevents the risk of interlayer peeling, greatly improving the service life and reliability of the product. Secondly, the wavy interface helps to relieve interlayer stress. During the use of the printed nickel mesh, stress may be generated between different material layers due to the difference in thermal expansion coefficient. The wavy interface can better disperse and absorb these stresses, reduce stress concentration, and thus improve the fatigue resistance and durability of the material. In addition, this interface structure can also enhance the overall flexibility of the composite printed nickel mesh. The wavy interface allows a certain degree of elastic deformation space to be provided while maintaining structural integrity, so that the printed nickel mesh has better adaptability when subjected to external forces. This design may also bring unexpected synergistic effects. For example, the wavy interface may affect the growth pattern of the electroplated chromium layer, promote the formation of a denser and more uniform chromium layer structure, and further improve the wear resistance and corrosion resistance of the surface. At the same time, this interface structure may change the thermal and electrical conductivity of the material at the microscopic scale, bringing new functional advantages to the printed nickel mesh. In general, the wavy interface design between the electroplated nickel layer and the electroplated chromium layer is a versatile and efficient innovation. It not only enhances the interlayer bonding and improves the stability of the overall structure, but also comprehensively improves the comprehensive performance of the composite printed nickel mesh through stress dispersion, flexibility improvement and potential synergistic effects, providing new ideas and methods for the design and preparation of high-performance printed nickel mesh.

[0013] Furthermore, the thickness of the printed nickel mesh substrate is 40-50 μm, and the thickness of the electroplated nickel layer is 60-80 μm; The thickness of the electroplated chromium layer is 20-45 μm; the thickness of the photosensitive resin layer is 15-35 μm.

[0014] First, the thickness of the printed nickel mesh substrate and the electroplated nickel layer are controlled at 40~50μm and 60~80μm respectively, which is designed to provide sufficient mechanical strength and corrosion resistance. The thickness of the electroplated chromium layer is controlled at 20-45μm, providing excellent surface hardness and wear resistance for the entire structure.

[0015] Furthermore, the preparation method of the photosensitive resin layer comprises the following steps: by weight, 20 to 45 parts of polyurethane-acrylate prepolymer, 0.5 to 2.0 parts of 1-hydroxycyclohexyl phenyl ketone and 15 to 30 parts of mercapto silicone resin are mixed at a speed of 2000 to 3000 r / min for 30 to 60 minutes, and then coated on the electroplated chromium layer, and then irradiated at a wavelength of 365 nm and a radiation intensity of 8.0 to 10.5 mW.cm −2 It is cured under ultraviolet light for 30 to 45 seconds, and a photosensitive resin layer is obtained after complete curing.

[0016] The preparation method of the photosensitive resin layer ensures the uniformity of the resin layer and the consistency of performance by precisely controlling the mixing ratio, rotation speed, mixing time and curing conditions of the polyurethane-acrylate prepolymer and the mercapto silicone resin.

[0017] Furthermore, the preparation method of the polyurethane-acrylate prepolymer comprises the following steps: by weight, adding 15 to 25 parts of polytetramethylene ether glycol, 0.20 to 0.30 parts of trimethylolpropane, and 0.015 to 0.025 parts of dibutyltin dilaurate into a three-necked flask, stirring and mixing, and heating to 55 to 65° C., then dripping 5.0 to 9.0 parts of isophorone diisocyanate dropwise, then stirring the resulting mixture at 55 to 65° C. for 60 to 120 minutes, then adding 4.0 to 8.0 parts of hydroxypropyl acrylate, continuing to stir for 30 to 45 minutes, and finally treating at 110 to 120° C. and 120 to 130 mmHg pressure for 60 to 120 minutes to remove the raw material residues in the resulting mixture to generate a transparent and viscous polyurethane-acrylate prepolymer; The preparation method of the mercapto silicone resin comprises the following steps: by weight, adding 150-170 parts of dimethyldiethoxysilane, 75-85 parts of methyltrimethoxysilane, 180-200 parts of 3-(trimethoxysilyl)-1-propanethiol and 210-230 parts of toluene into a three-necked flask, stirring and mixing and heating to 45-55° C., then dropwise adding 150-170 parts of hydrochloric acid with a mass fraction of 5-10%, then stirring the obtained mixture at 55-65° C. for 240-360 min, then standing and stratifying, separating the aqueous phase and the organic phase, retaining the organic phase, then washing the organic phase with water until it is neutral, and finally performing a reduced pressure concentration treatment at 110-120° C. and a pressure of 120-130 mmHg for 120-240 min to remove the solvent and volatile by-products in the organic phase to obtain a transparent mercapto silicone resin.

[0018] The preparation of the polyurethane-acrylate prepolymer of the present invention involves the precise proportion of various raw materials and the control of reaction conditions, aiming to obtain an ideal molecular structure and performance, and providing a good matrix for the cross-linking reaction of the resin layer. The preparation of the mercapto silicone resin also involves the precise proportion of various silane compounds and the control of reaction conditions, aiming to obtain a product with a specific structure and reaction activity.

[0019] In summary, the acid- and alkali-resistant high-strength composite printed nickel mesh of the present invention achieves a comprehensive improvement in multiple performance indicators such as strength, corrosion resistance, and wear resistance of the composite printed nickel mesh through the setting of a multi-layer composite structure and the combination of its microscopic crystal structure characteristics. This innovative technical solution not only solves the problems of easy corrosion and insufficient strength of traditional printed nickel mesh in harsh environments, but also provides a new technical path for the preparation of high-performance printed nickel mesh. Through the synergistic effect between the functional layers, the present invention has successfully developed an acid- and alkali-resistant high-strength composite printed nickel mesh with excellent comprehensive performance.

[0020] The present invention also provides a method for preparing an acid- and alkali-resistant high-strength composite printed nickel mesh, comprising the following steps: S1, placing the core mold into a first nickel plating solution for nickel plating, separating the nickel mesh formed by nickel plating from the core mold to obtain a printed nickel mesh substrate; S2, placing the printed nickel mesh substrate in a second nickel plating solution for nickel plating, so that the surface of the printed nickel mesh substrate is covered with an electroplated nickel layer; then placing it in a chromium plating solution for chromium plating, so that the surface of the electroplated nickel layer is covered with an electroplated chromium layer; S3. preparing a photosensitive resin layer on the surface of the electroplated chromium layer.

[0021] Furthermore, in step S1, the composition of the first nickel plating solution includes: 140-150 g / L nickel sulfate, 38-42 g / L nickel chloride, 32-36 g / L boric acid, 0.26-0.30 g / L 1,4-butynediol, 0.08-0.12 g / L sodium dodecyl sulfate, 60-100 mg / L sodium thiazolinyl dithiopropane sulfonate, and the balance is water.

[0022] Furthermore, in step S1, the process parameters of nickel plating are: temperature of 40-45°C, current density of 2.5-3.5A / dm 2 , the electroplating time is 35~45min.

[0023] Further, in step S2, the composition of the second nickel plating solution includes: 140-150 g / L of nickel sulfate, 38-42 g / L of nickel chloride, 32-36 g / L of boric acid, 0.5-3.5 g / L of rare earth additive, 0.26-0.30 g / L of 1,4-butynediol, 0.08-0.12 g / L of sodium dodecyl sulfate, 60-100 mg / L of sodium thiazolinyl dithiopropane sulfonate, and the balance is water; the rare earth additive is a combination of one or both of lanthanum oxide and lanthanum chloride; The process parameters of nickel plating are: temperature 35~45℃, current density 8~12A / dm 2 , the electroplating time is 120~240min.

[0024] Further, in step S3, the composition of the chromium plating solution includes: 0.4-0.8 mol / L chromium sulfate, 0.7-1.2 mol / L formic acid, 0.8-1.2 mol / L ammonium chloride, 0.8-1.2 mol / L potassium chloride, 0.02-0.07 mol / L polyethylene glycol, and the balance is water; The process parameters of chrome plating are: temperature 55~65℃, current density 65~75A / dm 2 , the electroplating time is 40~70min.

[0025] The preparation method of the present invention comprises four main steps: preparing a printed nickel mesh substrate, preparing an electroplated nickel layer, preparing an electroplated chromium layer and preparing a photosensitive resin layer, and each step is carefully designed to achieve a specific function and produce a synergistic effect with other steps.

[0026] The printed nickel mesh substrate is prepared using a carefully formulated electroplating solution that contains nickel sulfate, nickel chloride, boric acid and other main ingredients, as well as additives such as 1,4-butynediol, sodium dodecyl sulfate and sodium thiazolinyl dithiopropane sulfonate; the purpose of these additives is to regulate the structure and properties of the coating, among which 1,4-butynediol may be used to improve the brightness and flatness of the coating, sodium dodecyl sulfate as a surfactant can improve the wettability of the electroplating solution, and sodium thiazolinyl dithiopropane sulfonate may be used to improve the ductility and toughness of the coating. Precise control of electroplating process parameters, including temperature, current density and electroplating time, aims to obtain the ideal coating thickness and structure.

[0027] The preparation of the electroplated nickel layer is a key innovation of the present invention. Rare earth additives (lanthanum oxide or lanthanum chloride or a mixture of the two) are added to the first nickel plating electroplating solution. The purpose of this design is to change the microstructure of the nickel layer by adding rare earth elements. Rare earth elements may promote the formation of an island-like growth columnar crystal structure by affecting the crystallization process of nickel. This special microstructure can not only improve the strength of the material, but also enhance its corrosion resistance. The process parameters of the electroplated nickel layer, especially the lower current density and the longer electroplating time, are further conducive to the formation of an ideal columnar crystal structure.

[0028] The electroplated chromium layer is prepared using a unique plating solution composition, including chromium sulfate, formic acid, ammonium chloride, potassium chloride and polyethylene glycol. This formulation is designed to obtain a high-quality chromium coating, in which formic acid may be used as a reducing agent, ammonium chloride and potassium chloride may be used to improve conductivity and improve coating quality, and polyethylene glycol may be used to adjust the stress of the coating and improve its brightness. The selection of electroplating process parameters, especially the higher current density, is aimed at obtaining a dense, hard chromium coating, thereby providing excellent surface hardness and wear resistance.

[0029] The multi-step preparation method of the present invention exhibits a significant synergistic effect. The printed nickel mesh substrate provides basic strength and corrosion resistance for the entire structure, the electroplated nickel layer further enhances these properties through a special microstructure, and the electroplated chromium layer provides excellent surface properties. The interface design between the layers, especially the wavy interface that may be formed between the electroplated nickel layer and the electroplated chromium layer, enhances the interlayer bonding strength and improves the stability of the overall structure.

[0030] Furthermore, the preparation of the photosensitive resin layer not only improves the comprehensive performance of the material, but also brings new functional possibilities to the printed nickel mesh.

[0031] In general, the present invention achieves a comprehensive improvement in multiple performance indicators of printed nickel mesh, such as strength, corrosion resistance, and wear resistance, through a carefully designed multi-step preparation method. Each step is precisely controlled, including the composition of the electroplating solution, the selection of additives, the setting of process parameters, etc., all of which are aimed at obtaining ideal microstructures and macroscopic properties. Through the synergistic effect between the functional layers, the present invention successfully developed an acid- and alkali-resistant, high-strength composite printed nickel mesh with excellent comprehensive performance. This innovative preparation method not only solves the problems of easy corrosion and insufficient strength of traditional printed nickel mesh in harsh environments, but also provides a new technical path for the preparation of high-performance printed nickel mesh, making important contributions to technological progress in related fields.

[0032] (3) Beneficial technical effects 1. In the composite printed nickel mesh of the present invention, the printed nickel mesh substrate and the electroplated nickel layer provide basic strength and corrosion resistance, the electroplated chromium layer increases the surface hardness and wear resistance, and the photosensitive resin layer further improves the comprehensive performance of the material. The present invention combines the polyurethane-acrylate prepolymer with the mercapto silicone resin through a mercapto-olefin click chemistry reaction to form a highly cross-linked and chemically resistant composite photosensitive resin layer, which significantly improves the performance and application range of the printed nickel mesh. The resin layer has excellent mechanical strength and chemical stability, and can be accurately cured during the printing process to form a high-resolution pattern. The precisely controlled preparation process ensures the uniformity and performance consistency of the resin layer.

[0033] 2. The present invention significantly improves the comprehensive performance of the nickel layer through innovative electroplating process design, and opens up a new path for the development of high-performance coating materials. Compared with traditional technologies, the electroplated nickel layer achieved by the present invention has a unique island-shaped growth columnar crystal structure and Luan crystal structure. This microstructure design brings many performance advantages. First, the island columnar crystal structure increases the surface area and improves the reaction activity, while effectively reducing the internal stress and enhancing the bonding force and stability of the coating. Secondly, the precisely controlled columnar crystal diameter (50~150nm) not only ensures the structural stability, but also maintains a high specific surface area and increases the contact area. Furthermore, the introduction of Luan crystal structure further enhances the mechanical properties and corrosion resistance of the coating, and improves the hardness, toughness and density. The synergistic effect of these structural features not only improves the mechanical strength of the coating, but also maintains good ductility, avoids the brittleness problem, and improves thermal stability and fatigue resistance.

[0034] 3. The present invention significantly improves the comprehensive performance of the composite printed nickel mesh by designing a wavy interface between the electroplated nickel layer and the electroplated chromium layer. This innovative structure increases the contact area between the layers, provides more mechanical interlocking points, greatly enhances the bonding force between the layers, effectively prevents interlayer peeling, and extends the service life of the product. The wavy interface can also better disperse and absorb interlayer stress, reduce stress concentration, and improve the material's fatigue resistance and durability. This design enhances the overall flexibility of the printed nickel mesh and provides a certain elastic deformation space, making it more adaptable when subjected to external forces. The wavy interface may promote the formation of a denser and more uniform chromium layer structure, further improving the surface wear resistance and corrosion resistance, and may change the thermal and electrical conductivity of the material on a microscopic scale, bringing new functional advantages.

[0035] 4. The acid-base resistant and high-strength composite printed nickel mesh proposed in the present invention achieves a comprehensive improvement in performance through a carefully designed multi-layer structure. The electroplated nickel layer provides basic strength and corrosion resistance. Its unique island columnar crystal structure and twin structure effectively hinder dislocation movement, improve yield strength and tensile strength, and at the same time, the nano-scale gap acts as a corrosion barrier to improve corrosion resistance. The wavy interface between the electroplated nickel layer and the chromium layer increases the contact area, disperses stress, and reduces the risk of peeling. The electroplated chromium layer provides excellent surface hardness and wear resistance. The innovative photosensitive resin layer is highly cross-linked through the click chemical reaction of polyurethane-acrylate prepolymer and mercapto silicone resin, providing mechanical properties, flexibility, heat resistance and chemical stability. The synergistic effect of each layer significantly improves the comprehensive performance of the printed nickel mesh, solving the problems of easy corrosion and insufficient strength of traditional technologies in harsh environments. The precisely controlled preparation process ensures the optimal ratio and performance of each component. This innovation provides high-performance solutions for high-end printing, electronics, medical and other fields, and is expected to promote technological upgrading and new application development in related industries. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a TEM image of the columnar crystal structure of the island-like growth of the electroplated nickel layer prepared in Example 1 of the present invention.

[0037] Figure 2 This is a TEM image of the twin structure of the electroplated nickel layer prepared in Example 1 of the present invention.

[0038] Figure 3 This is the phase XRD spectrum of the printed nickel mesh substrate and the electroplated nickel layer prepared in Example 1 of the present invention.

[0039] Figure 4 This is a TEM image of the interface between the electroplated nickel layer and the electroplated chromium layer prepared in Example 1 of the present invention.

[0040] Figure 5 This is an infrared Fourier spectrum FTIR graph of the photosensitive resin layer prepared in Example 1 of the present invention.

[0041] Figure 6 This is a TEM image of the electroplated nickel layer prepared in Comparative Example 1 of the present invention.

[0042] Figure 7 This is a TEM image of the interface between the electroplated nickel layer and the electroplated chromium layer prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0043] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0044] In the case of not specifying specific conditions, the operation in the embodiment is carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. The parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.

[0045] Table 1 Reagents required for the examples and comparative examples and the corresponding purchasing companies Embodiment 1: A high-strength, acid- and alkali-resistant composite printed nickel mesh comprises a printed nickel mesh substrate, wherein an electroplated nickel layer, an electroplated chromium layer and a photosensitive resin layer are sequentially arranged on the surface of the printed nickel mesh substrate from the inside to the outside; the electroplated nickel layer contains an island-like columnar crystal structure with an average diameter of 50 nm, and the electroplated nickel layer also contains a twin structure; the interface between the electroplated nickel layer and the electroplated chromium layer is wavy; the thickness of the printed nickel mesh substrate and the electroplated nickel layer are 40 μm and 60 μm respectively; the thickness of the electroplated chromium layer is 20 μm; and the thickness of the photosensitive resin layer is 15 μm.

[0046] The photosensitive resin layer of this embodiment is obtained by a thiol-olefin click chemical reaction of a polyurethane-acrylate prepolymer and a mercapto silicone resin. The specific preparation method of the photosensitive resin layer includes the following steps: (1) In parts by weight, 15 parts of polytetramethylene ether glycol, 0.20 parts of trimethylolpropane and 0.015 parts of dibutyltin dilaurate were added into a 100 mL three-necked flask, stirred and mixed and heated to 55° C., then 5.0 parts of isophorone diisocyanate were added dropwise, and the resulting mixture was stirred at 55° C. for 60 min, then 4.0 parts of hydroxypropyl acrylate were added, and stirring was continued for 30 min. Finally, the mixture was treated at 110° C. and 120 mmHg pressure for 60 min to remove the raw material residues in the mixture, thereby generating a transparent and viscous polyurethane-acrylate prepolymer.

[0047] (2) 150 parts of dimethyldiethoxysilane, 75 parts of methyltrimethoxysilane, 180 parts of 3-(trimethoxysilyl)-1-propanethiol and 210 parts of toluene were added to a 1000 mL three-necked flask, stirred and mixed and heated to 45°C, and then 150 parts of 5% by mass hydrochloric acid were added dropwise. Subsequently, the mixture was stirred at 55°C for 240 minutes, and then after standing and stratification, the aqueous phase and the organic phase were separated, the organic phase was retained, and then the organic phase was washed with water until it was neutral. Finally, it was concentrated under reduced pressure at 110°C and 120 mmHg for 120 minutes to remove the solvent and volatile by-products in the organic phase to obtain a transparent mercapto silicone resin.

[0048] (3) 20 parts of polyurethane-acrylate prepolymer, 0.5 parts of 1-hydroxycyclohexyl phenyl ketone and 15 parts of mercapto silicone resin were mixed at a speed of 2000 r / min for 30 min, and then coated on the electroplated chrome layer. −2 The film is cured under ultraviolet light for 30 seconds, and a photosensitive resin layer is obtained after complete curing.

[0049] This embodiment also provides a method for preparing an acid- and alkali-resistant high-strength composite printed nickel mesh, comprising the following steps: S1. Preparing a printed nickel mesh substrate: placing a core mold into a first nickel plating solution for nickel plating, and separating the nickel mesh formed by the nickel plating from the core mold to obtain a printed nickel mesh substrate.

[0050] The first nickel plating solution is composed of: 140 g / L nickel sulfate, 38 g / L nickel chloride, 32 g / L boric acid, 0.26 g / L 1,4-butynediol, 0.08 g / L sodium dodecyl sulfate, 60 mg / L sodium thiazoline dithiopropane sulfonate, and the balance is water. The process parameters of nickel plating are: temperature 40 ° C, current density 2.5 A / dm 2 , electroplating time 35min.

[0051] S2, placing the printed nickel mesh substrate in a second nickel plating solution for nickel plating, so that the surface of the printed nickel mesh substrate is covered with an electroplated nickel layer; then placing it in a chromium plating solution for chromium plating, so that the surface of the electroplated nickel layer is covered with an electroplated chromium layer; The composition of the second nickel plating solution includes: nickel sulfate 140g / L, nickel chloride 38g / L, boric acid 32g / L, lanthanum oxide 0.5g / L, 1,4-butynediol 0.26g / L, sodium dodecyl sulfate 0.08g / L, sodium thiazoline dithiopropane sulfonate 60mg / L, and the balance is water. The process parameters of nickel plating are: temperature 35°C, current density 8A / dm 2 , electroplating time 120min; The composition of the electroplating solution for the chromium layer includes: 0.4 mol / L chromium sulfate, 0.7 mol / L formic acid, 0.8 mol / L ammonium chloride, 0.8 mol / L potassium chloride, 0.02 mol / L polyethylene glycol, and the balance is water. The process parameters for chromium plating are: temperature 55°C, current density 65A / dm 2 , electroplating time 40min.

[0052] S3, preparing a photosensitive resin layer: preparing a photosensitive resin layer on the surface of the electroplated chromium layer (preparing the photosensitive resin layer according to the method in step (3) of this embodiment).

[0053] The present invention has powerfully proved its unique structural design and excellent performance through a series of experimental results and analytical data.

[0054] Figure 1 The TEM image clearly shows the island columnar crystal structure of the electroplated nickel layer, which is beneficial to improving the mechanical strength and corrosion resistance of the coating.

[0055] Figure 2 The TEM image reveals the twin structure in the electroplated nickel layer, which can significantly enhance the overall performance of the coating.

[0056] Figure 3 The XRD patterns of the printed nickel mesh substrate and the electroplated nickel layer were compared, providing direct evidence for the difference in the two-layer structure.

[0057] Figure 4 The wavy interface between the electroplated nickel layer and the electroplated chromium layer is shown. This special interface structure helps to enhance the interlayer bonding and improve the overall performance.

[0058] Figure 5 The FTIR spectrum of the photosensitive resin layer was analyzed in detail for its chemical composition and reaction degree. -1 、1730cm -1 and 1531cm -1 The characteristic absorption peaks at 2260-2280cm correspond to the polyether segment, carbonyl group and NH group of polyurethane, respectively, confirming the expected chemical structure. -1 The absence of the characteristic absorption peak of isocyanate group in the range and the 1635cm -1 and 813cm -1 The disappearance of CC and CH characteristic absorption strongly proves the complete curing of the photosensitive resin. These results comprehensively show that the present invention successfully designs and prepares a composite coating with a special structure and excellent performance, providing sufficient scientific basis for its superiority in practical applications.

[0059] Embodiment 2: A high-strength, acid- and alkali-resistant composite printed nickel mesh comprises a printed nickel mesh substrate, wherein an electroplated nickel layer, an electroplated chromium layer and a photosensitive resin layer are sequentially arranged on the surface of the printed nickel mesh substrate from the inside to the outside; the electroplated nickel layer contains an island-like columnar crystal structure, the average diameter of the columnar crystal structure is 80 nm, and the electroplated nickel layer also contains a twin structure; the interface between the electroplated nickel layer and the electroplated chromium layer is wavy; the thickness of the printed nickel mesh substrate and the electroplated nickel layer are 43 μm and 66 μm respectively; the thickness of the electroplated chromium layer is 28 μm; and the thickness of the photosensitive resin layer is 21 μm.

[0060] The photosensitive resin layer of this embodiment is obtained by a thiol-olefin click chemical reaction of a polyurethane-acrylate prepolymer and a mercapto silicone resin; the specific preparation method of the photosensitive resin layer comprises the following steps: (1) In parts by weight, 18 parts of polytetramethylene ether glycol, 0.23 parts of trimethylolpropane and 0.018 parts of dibutyltin dilaurate were added into a 100 mL three-necked flask, stirred and mixed and heated to 58°C, then 6.2 parts of isophorone diisocyanate were added dropwise, and the resulting mixture was stirred at 58°C for 78 minutes, then 5.2 parts of hydroxypropyl acrylate were added, and stirring was continued for 35 minutes. Finally, the mixture was treated at 113°C and 123 mmHg for 80 minutes to remove the raw material residues in the mixture, thereby generating a transparent and viscous polyurethane-acrylate prepolymer.

[0061] (2) 156 parts of dimethyldiethoxysilane, 78 parts of methyltrimethoxysilane, 186 parts of 3-(trimethoxysilyl)-1-propanethiol and 216 parts of toluene were added to a 1000 mL three-necked flask, stirred and mixed and heated to 48°C, and then 156 parts of 6% by mass hydrochloric acid were added dropwise. Subsequently, the resulting mixture was stirred at 58°C for 276 min, and then after standing and stratification, the aqueous phase and the organic phase were separated, the organic phase was retained, and then the organic phase was washed with water until it was neutral. Finally, it was concentrated under reduced pressure at 113°C and 123 mmHg for 160 min to remove the solvent and volatile by-products in the organic phase to obtain a transparent mercapto silicone resin.

[0062] (3) 28 parts of polyurethane-acrylate prepolymer, 1.0 part of 1-hydroxycyclohexyl phenyl ketone and 20 parts of mercapto silicone resin were mixed at a speed of 2300 r / min for 39 minutes, and then coated on the electroplated chrome layer. −2 The film is cured under ultraviolet light for 35 seconds, and a photosensitive resin layer is obtained after complete curing.

[0063] This embodiment also provides a method for preparing an acid- and alkali-resistant high-strength composite printed nickel mesh, comprising the following steps: S1, preparing a printed nickel mesh substrate: placing a core mold into a first nickel plating solution for nickel plating, separating the nickel mesh formed by the nickel plating from the core mold, and obtaining a printed nickel mesh substrate; The first nickel plating solution is composed of: nickel sulfate 143g / L, nickel chloride 39g / L, boric acid 33g / L, 1,4-butynediol 0.27g / L, sodium dodecyl sulfate 0.09g / L, sodium thiazoline dithiopropane sulfonate 72mg / L, and the balance is water. The process parameters of nickel plating are: temperature 42°C, current density 2.8A / dm 2 , electroplating time 38min.

[0064] S2, placing the printed nickel mesh substrate in a second nickel plating solution for nickel plating, so that the surface of the printed nickel mesh substrate is covered with an electroplated nickel layer; then placing it in a chromium plating solution for chromium plating, so that the surface of the electroplated nickel layer is covered with an electroplated chromium layer.

[0065] The second nickel plating solution is composed of: nickel sulfate 143g / L, nickel chloride 39g / L, boric acid 33g / L, lanthanum chloride 1.4g / L, 1,4-butynediol 0.27g / L, sodium dodecyl sulfate 0.09g / L, sodium thiazoline dithiopropane sulfonate 72mg / L, and the balance is water. The process parameters of nickel plating are: temperature 38°C, current density 9A / dm 2 , electroplating time 156min; The composition of the electroplating solution for the chromium layer includes: 0.5 mol / L chromium sulfate, 0.9 mol / L formic acid, 0.9 mol / L ammonium chloride, 0.9 mol / L potassium chloride, 0.04 mol / L polyethylene glycol, and the balance is water. The process parameters for chromium plating are: temperature 58°C, current density 68A / dm 2 , electroplating time 49min.

[0066] S3, preparing a photosensitive resin layer: preparing a photosensitive resin layer on the surface of the electroplated chromium layer (preparing the photosensitive resin layer according to the method in step (3) of this embodiment).

[0067] Embodiment 3: A high-strength, acid- and alkali-resistant composite printed nickel mesh comprises a printed nickel mesh substrate, wherein an electroplated nickel layer, an electroplated chromium layer and a photosensitive resin layer are sequentially arranged on the surface of the printed nickel mesh substrate from the inside to the outside; the electroplated nickel layer is an island-like columnar crystal structure, and the average diameter of the columnar crystal structure is 110 nm; the interface between the electroplated nickel layer and the electroplated chromium layer is wavy; the thickness of the printed nickel mesh substrate and the electroplated nickel layer are 46 μm and 72 μm respectively; the thickness of the electroplated chromium layer is 35 μm; and the thickness of the photosensitive resin layer is 27 μm.

[0068] In this embodiment, the photosensitive resin layer is obtained by a thiol-olefin click chemical reaction of a polyurethane-acrylate prepolymer and a mercapto silicone resin; the preparation method of the photosensitive resin layer specifically comprises the following steps: (1) In parts by weight, 21 parts of polytetramethylene ether glycol, 0.26 parts of trimethylolpropane and 0.021 parts of dibutyltin dilaurate were added into a 100 mL three-necked flask, stirred and mixed and heated to 61°C, then 7.4 parts of isophorone diisocyanate were added dropwise, and the resulting mixture was stirred continuously at 61°C for 96 minutes, then 6.4 parts of hydroxypropyl acrylate were added, and stirring was continued for 40 minutes. Finally, the mixture was treated at 116°C and 126 mmHg for 100 minutes to remove the raw material residues in the mixture, thereby generating a transparent and viscous polyurethane-acrylate prepolymer.

[0069] (2) 162 parts of dimethyldiethoxysilane, 81 parts of methyltrimethoxysilane, 192 parts of 3-(trimethoxysilyl)-1-propanethiol and 222 parts of toluene were added to a 1000 mL three-necked flask, the mixture was stirred and heated to 51°C, and then 162 parts of 9% by mass hydrochloric acid were added dropwise. Subsequently, the resulting mixture was stirred at 61°C for 312 min, and then after standing and stratification, the aqueous phase and the organic phase were separated, the organic phase was retained, and then the organic phase was washed with water until neutral, and finally the organic phase was concentrated under reduced pressure at 116°C and 126 mmHg for 200 min to remove the solvent and volatile by-products in the organic phase to obtain a transparent mercapto silicone resin.

[0070] (3) 35 parts of polyurethane-acrylate prepolymer, 1.5 parts of 1-hydroxycyclohexyl phenyl ketone and 24 parts of mercapto silicone resin were mixed at a speed of 2600 r / min for 48 min, and then coated on the electroplated chrome layer. −2 The film was cured under ultraviolet light for 39 seconds, and a photosensitive resin layer was obtained after complete curing.

[0071] This embodiment also provides a method for preparing an acid- and alkali-resistant high-strength composite printed nickel mesh, comprising the following steps: S1, preparing a printed nickel mesh substrate: placing a core mold into a first nickel plating solution for nickel plating, separating the nickel mesh formed by the nickel plating from the core mold, and obtaining a printed nickel mesh substrate; The first nickel plating solution is composed of: 146 g / L nickel sulfate, 40 g / L nickel chloride, 34 g / L boric acid, 0.28 g / L 1,4-butynediol, 0.10 g / L sodium dodecyl sulfate, 84 mg / L sodium thiazoline dithiopropane sulfonate, and the balance is water. The process parameters of nickel plating are: temperature 43 ° C, current density 3.1 A / dm 2 , electroplating time 41min.

[0072] S2, placing the printed nickel mesh substrate in a second nickel plating solution for nickel plating, so that the surface of the printed nickel mesh substrate is covered with an electroplated nickel layer; then placing it in a chromium plating solution for chromium plating, so that the surface of the electroplated nickel layer is covered with an electroplated chromium layer; The second nickel plating solution is composed of: 146g / L nickel sulfate, 40g / L nickel chloride, 34g / L boric acid, 2.3g / L rare earth additive, 0.28g / L 1,4-butynediol, 0.10g / L sodium dodecyl sulfate, 84mg / L sodium thiazoline dithiopropane sulfonate, and the balance is water; the rare earth additive is lanthanum oxide and lanthanum chloride mixed in a mass ratio of 3:7. The process parameters of nickel plating are: temperature 41°C, current density 10A / dm 2 , electroplating time 192min.

[0073] The composition of the electroplating solution for the chromium layer includes: 0.6 mol / L chromium sulfate, 1.0 mol / L formic acid, 1.0 mol / L ammonium chloride, 1.0 mol / L potassium chloride, 0.05 mol / L polyethylene glycol, and the balance is water. The process parameters for chromium plating are: temperature 61°C, current density 71A / dm 2 , electroplating time 58min.

[0074] S3, preparing a photosensitive resin layer: preparing a photosensitive resin layer on the surface of the electroplated chromium layer (preparing the photosensitive resin layer according to the method in step (3) of this embodiment).

[0075] Embodiment 4: A high-strength, acid- and alkali-resistant composite printed nickel mesh comprises a printed nickel mesh substrate, wherein an electroplated nickel layer, an electroplated chromium layer and a photosensitive resin layer are sequentially arranged on the surface of the printed nickel mesh substrate from the inside to the outside; the electroplated nickel layer contains an island-like columnar crystal structure, the average diameter of the columnar crystal structure is 150nm, and the electroplated nickel layer also contains a twin structure; the interface between the electroplated nickel layer and the electroplated chromium layer is wavy; the thickness of the printed nickel mesh substrate and the electroplated nickel layer are 50μm and 80μm respectively; the thickness of the electroplated chromium layer is 45μm; and the thickness of the photosensitive resin layer is 35μm.

[0076] In this embodiment, the photosensitive resin layer is obtained by a thiol-olefin click chemical reaction of a polyurethane-acrylate prepolymer and a mercapto silicone resin; the preparation method of the photosensitive resin layer specifically comprises the following steps: (1) In parts by weight, 25 parts of polytetramethylene ether glycol, 0.30 parts of trimethylolpropane and 0.025 parts of dibutyltin dilaurate were added into a 100 mL three-necked flask, stirred and mixed and heated to 65°C, then 9.0 parts of isophorone diisocyanate were added dropwise, and the resulting mixture was stirred at 65°C for 120 min, then 8.0 parts of hydroxypropyl acrylate were added, and stirring was continued for 45 min. Finally, the mixture was treated at 120°C and 130 mmHg for 120 min to remove the raw material residues in the mixture, thereby generating a transparent and viscous polyurethane-acrylate prepolymer.

[0077] (2) 170 parts of dimethyldiethoxysilane, 85 parts of methyltrimethoxysilane, 200 parts of 3-(trimethoxysilyl)-1-propanethiol and 230 parts of toluene were added to a 1000 mL three-necked flask, the mixture was stirred and heated to 55°C, and then 170 parts of 10% by mass hydrochloric acid were added dropwise. Subsequently, the resulting mixture was stirred at 65°C for 360 min, and then after standing and stratification, the aqueous phase and the organic phase were separated, the organic phase was retained, and then the organic phase was washed with water until it was neutral, and finally the organic phase was concentrated under reduced pressure at 120°C and 130 mmHg for 240 min to remove the solvent and volatile by-products in the organic phase to obtain a transparent mercapto silicone resin.

[0078] (3) 45 parts of polyurethane-acrylate prepolymer, 2.0 parts of 1-hydroxycyclohexyl phenyl ketone and 30 parts of mercapto silicone resin were mixed at a speed of 3000 r / min for 60 min, and then coated on the electroplated chrome layer. −2 The film is cured under ultraviolet light for 45 seconds, and a photosensitive resin layer is obtained after complete curing.

[0079] This embodiment also provides a method for preparing an acid- and alkali-resistant high-strength composite printed nickel mesh, comprising the following steps: S1, preparing a printed nickel mesh substrate: placing a core mold into a first nickel plating solution for nickel plating, separating the nickel mesh formed by the nickel plating from the core mold, and obtaining a printed nickel mesh substrate; The first nickel plating solution is composed of: nickel sulfate 150g / L, nickel chloride 42g / , boric acid 36g / L, 1,4-butynediol 0.30g / L, sodium dodecyl sulfate 0.12g / L, sodium thiazoline dithiopropane sulfonate 100mg / L, and the balance is water. The process parameters of nickel plating are: temperature 45°C, current density 3.5A / dm 2 , electroplating time 45min.

[0080] S2, placing the printed nickel mesh substrate in a second nickel plating solution for nickel plating, so that the surface of the printed nickel mesh substrate is covered with an electroplated nickel layer; then placing it in a chromium plating solution for chromium plating, so that the surface of the electroplated nickel layer is covered with an electroplated chromium layer; The second nickel plating solution comprises: 150 g / L nickel sulfate, 42 g / L nickel chloride, 36 g / L boric acid, 3.5 g / L rare earth additive, 0.30 g / L 1,4-butynediol, 0.12 g / L sodium dodecyl sulfate, 100 mg / L sodium thiazolyl dithiopropane sulfonate, and the balance is water; the rare earth additive is a mixture of lanthanum oxide and lanthanum chloride in a mass ratio of 5:5; the process parameters of nickel plating are: temperature 45°C, current density 12 A / dm 2 , electroplating time 240min.

[0081] The composition of the electroplating solution for the chromium layer includes: 0.8 mol / L chromium sulfate, 1.2 mol / L formic acid, 1.2 mol / L ammonium chloride, 1.2 mol / L potassium chloride, 0.07 mol / L polyethylene glycol, and the balance is water. The process parameters for chromium plating are: temperature 65°C, current density 75A / dm 2 , electroplating time 70min.

[0082] S4, preparing a photosensitive resin layer: preparing a photosensitive resin layer on the surface of the electroplated chromium layer (preparing the photosensitive resin layer according to the method in step (3) of this embodiment).

[0083] Comparative Example 1: The same as Example 1, except that when preparing the electroplated nickel layer, no rare earth additive was added to the second nickel plating solution, so Figure 6 Transmission electron microscopy characterization shows that the electroplated nickel layer does not obtain a twin structure.

[0084] Comparative Example 2: The same as Example 1, except that when preparing the electroplated nickel layer, the current density is 1A / dm 2 , the electroplating time is 480min, so the electroplated nickel layer does not obtain an island columnar crystal structure, so Figure 7 Transmission electron microscopy shows that the interface between the electroplated nickel layer and the electroplated chromium layer is a straight line.

[0085] Comparative Example 3: The method is basically the same as Example 1, except that when preparing the photosensitive resin layer, the amount of 3-(trimethoxysilyl)-1-propanethiol added is 130 parts.

[0086] Performance Test: The solvent resistance test of printed nickel mesh includes four aspects: water resistance, acid resistance, oil resistance and alkali resistance, all of which are evaluated by immersion method. The water resistance test follows the GB / T1733-1993 standard, immersing in distilled water or deionized water at 23±2℃ for 30 days; the acid resistance and alkali resistance tests are carried out according to the GB / T9274-1988 method A, immersing in 10% concentration of sulfuric acid and sodium hydroxide solution for 30 days respectively; the oil resistance test also refers to the GB / T9274-1988 method A, but immersing in 120# gasoline for 168 hours.

[0087] After all tests are completed, the samples are wiped dry with filter paper and visually observed under diffused sunlight. The evaluation criteria are: no abnormality in the water resistance test is qualified; discoloration and gloss loss are allowed in the acid and oil resistance tests; slight discoloration and slight gloss loss are allowed in the alkali resistance test. In addition, if there are no obvious abnormalities in the paint film such as blistering, cracking, peeling, rusting, etc., it can be rated as "no abnormality", which means it has passed the test. This comprehensive test method comprehensively evaluates the performance of printed nickel screens in various solvent environments.

[0088] Tensile strength: The tensile strength test of printed nickel mesh is usually carried out with reference to the standard GB / T228-2010 "Tensile test of metallic materials Part 1: Room temperature test method".

[0089] Peel strength: The peel strength test uses a soft substrate peeling fixture and follows the IPC-TM-650 standard to measure the adhesion strength between the resin layer and the printed nickel mesh substrate by peeling the polyimide film at a 90° angle. The result is expressed in N / mm.

[0090] Nickel residue: The nickel residue test is carried out in accordance with GB / T18885-2020 "Technical Requirements for Ecological Textiles", and the test sample is a coating woven printed fabric after continuous printing for 30,000 meters. This comprehensive test method not only evaluates the mechanical properties of the photosensitive resin layer, but also pays attention to its possible environmental impact during long-term use, reflecting a comprehensive consideration of product quality and environmental safety.

[0091] The properties of the printed nickel screens of Examples 1 to 4 and Comparative Examples 1 to 3 are summarized in Table 2.

[0092] Table 2 Performance of printed nickel screens of Examples 1 to 4 and Comparative Examples 1 to 3 The main difference between Comparative Example 1 and Example 1 is that no rare earth additive is added in the preparation of the electroplated nickel layer, so the electroplated nickel layer does not obtain a twin structure. As can be seen from Table 2, the tensile strength and peel strength of Comparative Example 1 are also low, while the nickel residue is high. This is because the twin structure can significantly improve the mechanical properties and acid corrosion resistance of the nickel layer. The twin structure improves the strength and toughness of the nickel layer by increasing the number of grain boundaries, while also increasing the barrier capacity to acid-resistant corrosion media. Without the twin structure, the nickel layer is more susceptible to erosion by environmental factors, resulting in a decrease in various performances.

[0093] The main difference between Comparative Example 2 and Example 1 is the current density and electroplating time for preparing the electroplated nickel layer, which results in the electroplated nickel layer not obtaining an island columnar crystal structure, and the interface between the electroplated nickel layer and the electroplated chromium layer is linear. As can be seen from Table 2, this difference causes the acid resistance and alkali resistance of Comparative Example 2 to be lower than that of Example 1. At the same time, the tensile strength and peel strength of Comparative Example 2 are also lower, while the nickel residue is higher. This is because the island columnar crystal structure can significantly improve the mechanical properties and corrosion resistance of the nickel layer. The island columnar crystal structure provides a larger specific surface area and more grain boundaries, which enhances the strength and toughness of the nickel layer. In addition, the non-linear interface increases the bonding force between the nickel layer and the chromium layer, improving the overall performance.

[0094] The main difference between Comparative Example 3 and Example 1 is the amount of 3-(trimethoxysilyl)-1-propanethiol added in the preparation of the photosensitive resin layer. As can be seen from Table 2, this difference causes the water resistance, acid resistance, oil resistance and alkali resistance of Comparative Example 3 to be slightly reduced compared with Example 1. The tensile strength and peel strength of Comparative Example 3 are also slightly lower, while the nickel residue is slightly higher. This is because the amount of 3-(trimethoxysilyl)-1-propanethiol affects the content of thiol in the resin. An appropriate amount of thiol content can significantly improve the bonding force between the resin and the nickel layer and enhance the overall performance. Excessive thiol content may cause changes in the resin network structure, affecting its mechanical properties and corrosion resistance.

[0095] In summary, Example 1 is superior to all comparative examples in all performance indicators. This shows that by optimizing the structure of the electroplated nickel layer (such as adding rare earth elements to obtain a twin structure, adjusting the electroplating parameters to obtain an island columnar crystal structure), the comprehensive performance of the coating can be significantly improved. These optimization measures work together to improve the corrosion resistance, mechanical strength and bonding strength of the coating, while reducing the residual amount of nickel, thereby obtaining more excellent performance.

[0096] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.

Claims

1. An acid and alkali resistant high-strength composite printed nickel mesh, characterized in that: It comprises a printed nickel mesh substrate, wherein the surface of the printed nickel mesh substrate is sequentially provided with an electroplated nickel layer, an electroplated chromium layer and a photosensitive resin layer from the inside to the outside; The photosensitive resin layer is obtained from a polyurethane-acrylate prepolymer and a mercapto silicone resin through a mercapto-olefin click chemical reaction.

2. The acid-base resistant high-strength composite printed nickel mesh according to claim 1, characterized in that: The electroplated nickel layer contains an island-like columnar crystal structure, and the average diameter of the columnar crystal structure is 50-150 nm; the electroplated nickel layer also contains a crystalline structure; The interface between the electroplated nickel layer and the electroplated chromium layer is wavy.

3. The acid-base resistant high-strength composite printed nickel mesh according to claim 1, characterized in that: The thickness of the printed nickel mesh substrate is 40-50 μm, and the thickness of the electroplated nickel layer is 60-80 μm; The thickness of the electroplated chromium layer is 20-45 μm; the thickness of the photosensitive resin layer is 15-35 μm.

4. The acid-base resistant high-strength composite printed nickel mesh according to claim 1, characterized in that: The preparation method of the photosensitive resin layer comprises the following steps: mixing 20 to 45 parts of polyurethane-acrylate prepolymer, 0.5 to 2.0 parts of 1-hydroxycyclohexyl phenyl ketone and 15 to 30 parts of mercapto silicone resin at a rotation speed of 2000 to 3000 r / min for 30 to 60 minutes, coating the mixture on the electroplated chromium layer, and then irradiating the mixture at a wavelength of 365 nm and a radiation intensity of 8.0 to 10.5 mW.cm −2 It is cured under ultraviolet light for 30 to 45 seconds, and a photosensitive resin layer is obtained after complete curing.

5. The acid-base resistant high-strength composite printed nickel mesh according to claim 1 or 4, characterized in that: The preparation method of the polyurethane-acrylate prepolymer comprises the following steps: adding 15-25 parts of polytetramethylene ether glycol, 0.20-0.30 parts of trimethylolpropane, and 0.015-0.025 parts of dibutyltin dilaurate into a three-necked flask by weight, stirring and mixing, and heating to 55-65° C., then dripping 5.0-9.0 parts of isophorone diisocyanate dropwise, then stirring the obtained mixture at 55-65° C. for 60-120 min, then adding 4.0-8.0 parts of hydroxypropyl acrylate, continuing to stir for 30-45 min, and finally treating at 110-120° C. and 120-130 mmHg pressure for 60-120 min to remove raw material residues in the obtained mixture to generate a transparent and viscous polyurethane-acrylate prepolymer; The preparation method of the mercapto silicone resin comprises the following steps: by weight, adding 150-170 parts of dimethyldiethoxysilane, 75-85 parts of methyltrimethoxysilane, 180-200 parts of 3-(trimethoxysilyl)-1-propanethiol and 210-230 parts of toluene into a three-necked flask, stirring and mixing and heating to 45-55° C., then dropwise adding 150-170 parts of hydrochloric acid with a mass fraction of 5-10%, then stirring the obtained mixture at 55-65° C. for 240-360 min, then standing and stratifying, separating the aqueous phase and the organic phase, retaining the organic phase, then washing the organic phase with water until it is neutral, and finally performing a reduced pressure concentration treatment at 110-120° C. and a pressure of 120-130 mmHg for 120-240 min to remove the solvent and volatile by-products in the organic phase to obtain a transparent mercapto silicone resin.

6. A method for preparing an acid-base resistant high-strength composite printed nickel mesh as described in any one of claims 1 to 5, characterized in that: The following steps are involved: S1, placing the core mold into a first nickel plating solution for nickel plating, separating the nickel mesh formed by nickel plating from the core mold to obtain a printed nickel mesh substrate; S2, placing the printed nickel mesh substrate in a second nickel plating solution for nickel plating, so that the surface of the printed nickel mesh substrate is covered with an electroplated nickel layer; then placing it in a chromium plating solution for chromium plating, so that the surface of the electroplated nickel layer is covered with an electroplated chromium layer; S3. preparing a photosensitive resin layer on the surface of the electroplated chromium layer.

7. The method for preparing an acid-base resistant high-strength composite printed nickel mesh according to claim 6, characterized in that: In the step S1, the composition of the first nickel plating electroplating solution includes: 140-150 g / L of nickel sulfate, 38-42 g / L of nickel chloride, 32-36 g / L of boric acid, 0.26-0.30 g / L of 1,4-butynediol, 0.08-0.12 g / L of sodium dodecyl sulfate, 60-100 mg / L of sodium thiazolinyl dithiopropane sulfonate, and the balance is water.

8. The method for preparing an acid-base resistant high-strength composite printed nickel mesh according to claim 6, characterized in that: In step S1, the process parameters of nickel plating are: temperature of 40-45°C, current density of 2.5-3.5A / dm 2 , the electroplating time is 35~45min.

9. The method for preparing an acid-base resistant high-strength composite printed nickel mesh according to claim 6, characterized in that: In the step S2, the composition of the second nickel plating electroplating solution includes: 140-150 g / L of nickel sulfate, 38-42 g / L of nickel chloride, 32-36 g / L of boric acid, 0.5-3.5 g / L of rare earth additive, 0.26-0.30 g / L of 1,4-butynediol, 0.08-0.12 g / L of sodium dodecyl sulfate, 60-100 mg / L of sodium thiazolinyl dithiopropane sulfonate, and the balance is water; the rare earth additive is a combination of one or both of lanthanum oxide and lanthanum chloride; The process parameters of nickel plating are: temperature 35~45℃, current density 8~12A / dm 2 , the electroplating time is 120~240min.

10. The method for preparing an acid-base resistant high-strength composite printed nickel mesh according to claim 6, characterized in that: In step S3, the composition of the chromium plating solution includes: 0.4-0.8 mol / L chromium sulfate, 0.7-1.2 mol / L formic acid, 0.8-1.2 mol / L ammonium chloride, 0.8-1.2 mol / L potassium chloride, 0.02-0.07 mol / L polyethylene glycol, and the balance is water; The process parameters of chrome plating are: temperature 55~65℃, current density 65~75A / dm 2 , the electroplating time is 40~70min.

Citation Information

Patent Citations

  • Multifunctional composite electrochemical deposition liquid and method of use thereof

    CN101250727A

  • Production process of low-stress electroforming printing nickel screen

    CN101812704A

  • Secondary chromeplating process of printing round-net die

    CN102925941A

  • Manufacture method of WK85 rotary printing screen

    CN105922716A

  • Novel environment-friendly nickel plating method

    CN115044944A